Kagiso Trust : investing for development impact - Urban, Boris; Beswick, Claire (London : SAGE Publications Ltd, 2017)
In November 2014, as the South African development agency, Kagiso Trust (KT) prepared to celebrate 30 years of existence in 2015, Themba Mola, KT's chief operating officer, reflected on the development work that the organisation had done since it started out in 1985. KT's intention was to bring about deep social and economic value in the communities it served through the programmes that it developed and funded. As Mola reviewed what KT had achieved, he asked himself whether the organisation needed to do anything differently to ensure that it continued and improved on the work it had been doing thus far.
Originally published in Urban, B., & Beswick, C. (2015). Kagiso Trust: Investing for development impact. WBS-2015-14. Johannesburg: The Case Centre, Wits Business School.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Kagiso Trust; Strategic planning -- South Africa; Industrial management -- South Africa